Cable armoring material formulation - WU HOUZHEN; SHAO WENZHEN (2016)
The invention discloses a cable armoring material formulation. A cable is made from, by mass, 30-40 parts of ramie fiber, 10-20 parts of organic tin, 10-20 parts of hard barium, 10-15 parts of a hot melt adhesive film, 10-20 parts of calcium stearate, 20-30 parts of a colorant, 10-20 parts of lead stearate and 10-15 parts of pottery clay. The cable armoring material formulation has the advantages of good insulating effect, wear resistance and high interference immunity. 本发明公开了种电缆铠装材料配方，所述电缆是由以下质量分的各原料构成：苎麻纤维30~40份、有机锡10~20份、硬钡10~20份、热熔胶膜10~15份、硬脂酸钙10~20份、着色剂20~30份、硬脂酸铅10~20份、陶土10~15份。本发明具有绝缘效果好、耐磨损和抗干扰性强等优点。